Gambaran Kualitas Hidup Lansia Yang Tinggal di Panti Sosial Tresna Werdha Yogyakarta Unit Budi Luhur - Putri, Dien Latif Nur Azizah; Akhmadi, Akhmadi; Subekti, Heru (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2008)
Please refer to the file